Antinociceptive effect of estriol and Glicina max l. (soya) in ovariectomized rats - Ángeles-Palacios, Reyna (2011)
Objective: To determine the protective effect of estriol and Glycine max L. (soybean) compared to nociceptive pain in ovariectomized rats. Design: Experimental study. Setting: Faculty of Medicine bioterium, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material: Holtzman albino female rats 2,5 to 3 months of age. Methods: The 29 rats were grouped randomly: group 1 (n = 8) non ovariectomized rats treated with saline (0.1 mL/kg); group 2 (n = 7) ovariectomized rats treated with saline (0.1 mL / kg); group 3 (n = 7) ovariectomized rats treated with estriol (0.2 mg/kg); group 4 (n = 7) ovariectomized rats treated with Glycine max L. (60 mg/kg). We determined baseline hotplate thermal pain as well as three days after treatment. Main outcome measures: Antinociceptive maximum efficacy (% AME). Results: We found that % EAM was higher in the non ovariectomized rats group (1.6%) than in the ovariectomized group (0.8%). Furthermore, the percentage of EAM in ovariectomized rats treated with saline (0.8%) compared with the group treated with estriol (5.8%) and also the percentage of EAM in the Glycine max L. group (4.2%) was higher than in the ovariectomized group treated with saline (0.8%) but not higher than the group treated with estriol. Conclusions: Estriol and Glycine max L. have protective role against thermal nociceptive pain in ovariectomized rats.